Business Strategy on the Success of Sharia Securities Crowdfunding: Indonesian Sharia Crowdfunding Pioneer - Julia Famor Pratami; Pri Agung Danarahmanto; Nugraha Nugraha; Maya Sari (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Internet-based fundraising or commonly known as crowdfunding (CF) is currently a popular means for entrepreneurs to raise funds. The huge potential of the sharia economy encourages startup companies to establish sharia-based securities crowdfunding (SCF) companies. The purpose of this study is to provide an understanding of business strategies in order to achieve success in Islamic SCF companies in Indonesia. Design/methodology/approach: This research employed a qualitative research design with a case study approach on the first sharia SCF company in Indonesia named Shafiq. The data were collected by conducting in-depth interviews with the board of directors at Shafiq. Results: The research found that the success of Islamic SCF companies is triggered by the presence of teams, content, videos, platforms, use of social media, project quality, legality, business selection, and selection of sharia systems. In other words, this indicates that the factors of trust and security for both business actors and investors are the main factors that drive the success of sharia SCF companies. The novelty of this research is obtained by using a qualitative case study method to analyze the business strategy of Islamic securities crowdfunding, and there are no researchers who have investigated the strategy of Shafiq's company as the first sharia SCF company in Indonesia. Paper type: Research paper